Prevalence and Factors Associated with Palliative Care Utilization among Hospitalized Patients with Esophageal Cancer in the United States. Issue 2 (April 2023) - Jackson, Inimfon; Jackson, Nsikak; Etuk, Aniekeme
Objective: Due to poor 5-year survival and high symptom burden, esophageal cancer (EC) patients benefit markedly from palliative care utilization. However, there is scant literature exploring factors associated with receipt of palliative care in this population. The prevalence of palliative care consultations among hospitalized EC patients was assessed. Furthermore, we examined the factors associated with palliative care utilization among hospitalized patients with EC.Methods: Retrospective analyses were conducted using the National Inpatient Sample data collected between 2016 and 2018. Descriptive analyses were used to explore the overall prevalence of palliative care utilization. Univariate and multivariable regression models were used to examine factors associated with palliative care utilization among hospitalized EC patients.Results: The overall prevalence of palliative care utilization was 15.97%. Non-Hispanic Blacks had 1.16 times (95% CI: 1.00-1.34) higher odds of palliative care utilization compared to non-Hispanic Whites. Compared to patients on Medicare, those on Medicaid (AOR: 1.21; 95% CI: 1.02-1.45), private (AOR: 1.19; 95% CI: 1.06-1.35) and other insurance types (AOR: 1.68; 95% CI: 1.39-2.02) were more likely to utilize palliative care. Relative to patients hospitalized in the Northeast, those in Midwest (AOR: 1.34; 95% CI: 1.17-1.53), south (AOR: 1.28; 95% CI: 1.12-1.45), and west (AOR: 1.41; 95% CI: 1.22-1.61) were more likely to receive palliative care. Patients admitted to urban teaching hospitals (AOR: 1.28; 95% CI: 1.07-1.52) had higher odds of having palliative care consultations when compared to their counterparts in rural hospitals. Also, patients who were either discharged to a facility/with home health (OR: 5.39; 95% CI: 4.76-6.10) or died during hospitalization (OR: 26.93; 95% CI: 23.31-31.11) had higher odds of utilizing palliative care when compared to those with a routine discharge. Other factors identified were median household income quartiles, admission type, chemotherapy receipt, and the number of comorbidities.Conclusions: Our findings highlight the need to further analyze and address factors that may hinder palliative care utilization among hospitalized EC patients to decrease disparities and improve their quality of life. Hospital physicians and health systems need to be more proactive about palliative care consultations to maximize the benefits to these sick cancer patients.